PEMBELAJARAN SAINS MENGGUNAKAN MEDIAKOTEKA SAINS (KOMIK TEMPEL KARTUN SAINS) PADA MATERI EKOSISTEM TERHADAP PRESTASI DAN KEAKTIFAN BELAJAR SISWA MTs AL MUJADDADIYYAH KOTA MADIUN - Riyan Yuniarga; Sri Utami (Jurnal Pendidikan, 2013)
The research aims to create a learning media Koteka Science ( Science Cartoons Comics Paste ) on the material terms of the ecosystem and the achievement of student learning MTs Al Mujaddadiyyah Madiun. The study was conducted in May-June 2013. Study uses quantitative data analysis techniques, namely the feasibility of data media Koteka Science from the validator, the data teacher activity , student activity data, the data student achievement data and teacher student questionnaire responses to the penis gourds. Science. Products validated by 3 validator and obtain tested 20 types of data, which is included in the criteria for 2 very worthy, worthy 6,7 pretty decent, 1 less feasible, and 4 are not feasible. The data indicate that overall for Science Koteka media worthy and well as learning media. Based on the pretest results of 22 students in the criteria either 10, 10 is good enough, and not good 2, whereas the posttest results of 22 students who fall into the criteria of an excellent 7, both 14, and a pretty good one. Data indicate that the Science koteka using instructional media can improve student achievement scores. Based on students' responses to the questionnaire Science Koteka media of 22 students, who fall into the category of very good 7 students , both 9 students , and quite 6 students. It shows that students' response to the media either Koteka Science. In response to the teacher questionnaire data showed that 80 % feasibility study. Student activities gained 67.9 % before treatment and after treatment gained 80 %. The observation of teacher activity obtained before treatment and after treatment 85.4 % 90.4 %. It shows that learning by using media Koteka Science and decent so as to improve the performance and activity of students' learning.